Animal models of absence epilepsies: What do they model and do sex and sex hormones matter? - ONAT, FİLİZ (ACADEMIC PRESS INC ELSEVIER SCIENCE, 2014)
While epidemiological data suggest a female prevalence in human childhood- and adolescence-onset typical absence epilepsy syndromes, the sex difference is less clear in adult-onset syndromes. In addition, although there are more females than males diagnosed with typical absence epilepsy syndromes, there is a paucity of studies on sex differences in seizure frequency and semiology in patients diagnosed with any absence epilepsy syndrome. Moreover, it is unknown if there are sex differences in the prevalence or expression of atypical absence epilepsy syndromes. Surprisingly, most studies of animal models of absence epilepsy either did not investigate sex differences, or failed to find sex-dependent effects. However, various rodent models for atypical syndromes such as the AY9944 model (prepubertal females show a higher incidence than prepubertal males), BN model (also with a higher prevalence in males) and the Gabral deletion mouse in the C57BL/6J strain offer unique possibilities for the investigation of the mechanisms involved in sex differences. Although the mechanistic bases for the sex differences in humans or these three models are not yet known, studies of the effects of sex hormones on seizures have offered some possibilities. The sex hormones progesterone, estradiol and testosterone exert diametrically opposite effects in genetic absence epilepsy and pharmacologically-evoked convulsive types of epilepsy models. In addition, acute pharmacological effects of progesterone on absence seizures during proestrus are opposite to those seen during pregnancy. 17 beta-Estradiol has anti-absence seizure effects, but it is only active in atypical absence models. It is speculated that the pro-absence action of progesterone, and perhaps also the delayed pro-absence action of testosterone, are mediated through the neurosteroid allopregnanolone and its structural and functional homolog, androstanediol. These two steroids increase extrasynaptic thalamic tonic GABAergic inhibition by selectively targeting neurosteroid-selective subunits of GABA(A) receptors (GABA(A)Rs). Neurosteroids also modulate the expression of GABA(A)R containing the gamma 2, alpha 4, and delta subunits. It is hypothesized that differences in subunit expression during pregnancy and ovarian cycle contribute to the opposite effects of progesterone in these two hormonal states. (C) 2014 Elsevier Inc All rights reserved.
Keywords: Genetic models; Absence epilepsy; Rats; WAG/Rij; Mice; Atypical absence models; Typical absence models; AY 9944; Sex differences; Puberty; Neurosteroids; Pregnancy; Ovarian cycle; GABA(A) receptors; Delta subunits; Alpha subunits; SPIKE-WAVE DISCHARGES; GABA(A) RECEPTOR GAMMA-2-SUBUNIT; SEIZURE SUSCEPTIBILITY; STEROID-HORMONES; AFTERDISCHARGE THRESHOLDS; GENERALIZED EPILEPSIES; SUBUNIT EXPRESSION; MATERNAL-BEHAVIOR; RETICULAR NUCLEUS; ANGELMAN SYNDROME